Panic on the streets of London: police, crime and the july 2005 terror attacks - Mirko Draca; Stephen Machin; Robert Witt (Institute for the Study of Labor (IZA), 2008)
In this paper we study the causal impact of police on crime by looking at what happened to crime before and after the terror attacks that hit central London in July 2005. The attacks resulted in a large redeployment of police officers to central London boroughs as compared to outer London - in fact, police deployment in central London increased by over 30 percent in the six weeks following the July 7 bombings. During this time crime fell significantly in central relative to outer London. Study of the timing of the crime reductions and their magnitude, the types of crime which were more likely to be affected and a series of robustness tests looking at possible biases all make us confident that our research approach identifies a causal impact of police on crime. Implementing an instrumental variable approach shows an elasticity of crime with respect to police of approximately -0.3, so that a 10 percent increase in police activity reduces crime by around 3 percent.
urn:nbn:de:101:1-20080320126
Keywords: H00; 360; Crime; police : terror attacks; Kriminalität; Polizei; Rechtsdurchsetzung; Kausalanalyse; London; Großbritannien